Evaluating Water Use Efficiency and Water Treatment Systems at 1×1000 MW Coal-Fired Power Plants to Achieve Zero Liquid Discharge at PT XYZ - Henry Prihartanto; Fauzan Romadlon; Dian Alviana (Balai Besar Standardisasi dan Pelayanan Jasa Pencegahan Pencemaran Industri, 2026)
Water-use efficiency is a strategic issue in large-scale coal-fired steam power plants, given the high operational water demand and the increasing need to implement the Zero Liquid Discharge (ZLD) concept. However, most previous studies have examined the performance of desalination systems, cooling processes, or wastewater treatment installations separately, thus failing to provide a comprehensive picture of water loss and Zero Liquid Discharge (ZLD) readiness at the system level. This study adopts an integrated operational water balance approach to analyse water-use efficiency, trace the main pathways of water loss, and evaluate the extent of Zero Liquid Discharge (ZLD) achieved at a 1×1000 MW coal-fired power plant (PT XYZ). A quantitative case study was conducted using four years of operational data (2019–2022) on seawater inflow, Reverse Osmosis (RO) performance, internal water-use patterns, and Wastewater Treatment Plant (WWTP) efficiency. The analysis results show that total water loss exceeded 60% of the annual volume of seawater taken, while the Reverse Osmosis (RO) recovery rate was low, at 6.07–6.19% during 2019–2021, before increasing to 11.85% in 2022. This condition indicates a significant gap between the system's actual performance and the Zero Liquid Discharge (ZLD) target. On the other hand, although the Wastewater Treatment Plant (WWTP) has consistently achieved pollutant removal efficiencies above 95%, its contribution to overall water recovery improvement remains relatively limited. These findings confirm that integrated water balance analysis can serve as an effective diagnostic tool for linking operational inefficiencies to Zero Liquid Discharge (ZLD) readiness levels and for providing lessons applicable to water management in power generation systems with high water-use intensity.